2021
DOI: 10.1111/jora.12656
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant Youth Resilience: Theoretical Considerations, Empirical Developments, and Future Directions

Abstract: Resilient adaptation among immigrant youth provides the foundation for healthy and productive adult lives. Great diversity is observed in their adaptation. This diversity has been studied during the past decade from different angles and intellectual traditions. However, the results are disconnected. In this paper, first, we present a resilience conceptual model for understanding immigrant youth adaptation. We argue that its concepts and principles allow us to best pull together what is known and discover what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 142 publications
0
29
0
Order By: Relevance
“…A temporal perspective of acculturation allows researchers to integrate a more developmental understanding into studies of migration and acculturation, which has been advocated by developmental (e.g., Juang & Syed, 2019; Motti‐Stefanidi et al, 2021) and acculturation scholars (Ward & Szabó, 2019). This integration provides new perspectives on the outcomes studied.…”
Section: Timing Component Definition Measurement Examples Of Research...mentioning
confidence: 99%
“…A temporal perspective of acculturation allows researchers to integrate a more developmental understanding into studies of migration and acculturation, which has been advocated by developmental (e.g., Juang & Syed, 2019; Motti‐Stefanidi et al, 2021) and acculturation scholars (Ward & Szabó, 2019). This integration provides new perspectives on the outcomes studied.…”
Section: Timing Component Definition Measurement Examples Of Research...mentioning
confidence: 99%
“…To capture complex dynamic effects on immigrant youth adaptation, development, and acculturation, including bidirectional and cascade effects, as well as to disentangle developmental and acculturative change, a longitudinal design is required. However, a review of empirical articles focusing on individual differences in immigrant youth adaptation, published during the past decade, revealed that just over half of the studies had a longitudinal design (Motti-Stefanidi et al, 2021).…”
Section: Future Directionsmentioning
confidence: 99%
“…Immigrant children exhibit significant variation in their mental health outcomes despite disproportionate exposure to socio-economic adversity compared to their non-immigrant peers [ 1 ]. Identifying the factors that matter most for immigrant children’s mental health, particularly in their most proximal environments of the family and neighbourhood, can help to elucidate why some immigrant children thrive while others falter, which in turn can inform targets for interventions [ 2 ]. Such evidence has significant implications for immigrant-receiving societies such as Canada, where over a third of all children under 15 has at least one foreign‑born parent and population projections estimate that half will be of immigrant background by 2035 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%